Canada's big biblical bargain : how McGill University bought the Dead Sea scrolls - Kalman, Jason, 1974-; Du Toit, Jaqueline S., 1970- (Montréal : McGill-Queen's University Press, 2010)
Presents the story of Canada's attempt to purchase the greatest manuscript discovery of the twentieth century.
Introduction : "I should perhaps recall to you ..." -- "Telling tales of the early days" : McGill buys the Dead Sea Scrolls -- "We must ride out the crisis" : the efforts to bring the Dead Sea Scrolls to Montreal -- The real question : the nation, the object, and owning the past -- "The harvest of this patient waiting" -- Annotated correspondence -- Transcription of R.B.Y. Scott's handlist of Qumran cave four fragments purchased by McGill University as of May 1955.
Includes bibliographical references and index.
Print version record.
Keywords: Dead Sea scrolls; McGill University -- History -- 20th century; McGill University. -- Archives; McGill University. -- Faculty of Religious Studies -- Archives; Israel. -- Rashut ha-ʻatiḳot.; Israel. -- Rashut ha-ʻatiḳot.; McGill University; McGill University. -- Archives; McGill University. -- Faculty of Religious Studies; Dead Sea scrolls; McGill University -- History -- 20th century; McGill University. -- Archives; McGill University. -- Faculty of Religious Studies -- Archives; Israel. -- Rashut ha-atikot.; Acquisition of manuscripts -- Québec (Province) -- Montréal -- History -- 20th century; RELIGION -- Judaism -- Sacred Writings; SOCIAL SCIENCE -- Archaeology; Acquisition of manuscripts; Québec -- Montréal.; 1900-1999; JSTOR-DDA; Dead Sea scrolls. 4Q; Acquisition of manuscripts -- Québec (Province) -- Montréal -- History -- 20th century; Scott, R.B.Y. (Robert Balgarnie Young), 1899 -- Correspondence; Cultural property -- Protection -- Jordan -- History; McGill University -- History -- 20th century; McGill University. Archives; McGill University. Faculty of Religious Studies -- Archives; Israel. Rashut ha-atikot; Acquisition of manuscripts -- Québec (Province) -- Montréal -- History -- 20th century -- Sources; Multi-User.; Electronic books; Archives; History; Electronic books; Electronic books